2023
DOI: 10.3390/polym15071629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathode GDL Gradient Porosity Distribution along the Flow Channel Direction on Gas–Liquid Transport and Performance of PEMFC

Abstract: The gas diffusion layer (GDL) is an important component of proton exchange membrane fuel cells (PEMFCs), and its porosity distribution has considerable effects on the transport properties and durability of PEMFCs. A 3-D two-phase flow computation fluid dynamics model was developed in this study, to numerically investigate the effects of three different porosity distributions in a cathode GDL: gradient-increasing (Case 1), gradient-decreasing (Case 3), and uniform constant (Case 2), on the gas–liquid transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…where k ele , k ion , ϕ ele , ϕ ion , S ele , S ion represent electron conductivity, proton conductivity, solid phase potential, membrane potential, electron source term, and proton source term, respectively. The description of the details of all the source terms can be referred to in [43,44].…”
Section: Charge Conservation Equationmentioning
confidence: 99%
“…where k ele , k ion , ϕ ele , ϕ ion , S ele , S ion represent electron conductivity, proton conductivity, solid phase potential, membrane potential, electron source term, and proton source term, respectively. The description of the details of all the source terms can be referred to in [43,44].…”
Section: Charge Conservation Equationmentioning
confidence: 99%
“…They investigate the effects of wetting characteristics of the GDL, the current density, and the GDL porosity on the liquid water saturation and the performance of the PEM fuel cell. Many other experimental and numerical works [25][26][27][28][29][30][31] demonstrated that a gradient in the porosity of the GDL improves liquid water removal and gas reactant transport in the GDL of the PEMFC.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber paper (CFP), with the properties of high porosity, good electrical conductivity, excellent mechanical strength, outstanding corrosion resistance, etc. [1], has become the ideal material as a gas diffusion layer (GDL) of proton exchange membrane fuel cells (PEMFCs) and provides reactant and product permeability, transport of electrons, and heat and support of membrane electrode assembly (MEA) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%